2014
DOI: 10.1177/1087054713517542
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Methylphenidate on Default-Mode Network/Task-Positive Network Synchronization in Children With ADHD

Abstract: Although results should be interpreted cautiously because the sample size is small, they suggest that a failure of the TPN/DMN synchronization could be involved in the moment-to-moment variability in ADHD. Methylphenidate initiated TPN/DMN synchronization, which in turn appeared to reduce variability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 47 publications
4
36
0
Order By: Relevance
“…There it was found that the neurotypical pattern of integration within the DMN and segregation of the DMN from attention networks is reduced in youth with ADHD, which is highly similar to our present results involving component A. Other nondevelopmental studies in youths 69,70 and adults 71-73 have also found alterations in DMN-attention network interconnections in ADHD. 67 …”
Section: Discussionsupporting
confidence: 91%
“…There it was found that the neurotypical pattern of integration within the DMN and segregation of the DMN from attention networks is reduced in youth with ADHD, which is highly similar to our present results involving component A. Other nondevelopmental studies in youths 69,70 and adults 71-73 have also found alterations in DMN-attention network interconnections in ADHD. 67 …”
Section: Discussionsupporting
confidence: 91%
“…Neuroimaging studies [126][127][128] have shown that individuals with ADHD have reduced functional independence between task-positive networks and the task-negative DMN compared with individuals without ADHD; these networks have an anti-correlated relationship during successful spatial attention 129 and cognitive control 130 …”
Section: Fugl-meyer Scoresmentioning
confidence: 99%
“…A failure of the anti-phase synchronization between default-mode network (DMN) and task-positive networks (TPN) may be involved in the manifestation of ADHD. MPH affects DMN/TPN synchronization in patients with ADHD (Querne et al, 2014;Liddle et al, 2011). However, treatment with ATX made the relationship between the DMN and TPN less correlated (Lin, 2015).…”
Section: Discussionmentioning
confidence: 97%